The Weak Sustainability of the Salmon Feed Transition in Norway – A Bioeconomic Case Study - Hansen, Lillian (Frontiers in Marine Science, 2019)
This paper investigates transition pathways using an example from the bioeconomy: salmon farming and feed development in Norway. With a Multi-Level Perspective (MLP), the analysis show how a crucial biological input factor, feed, was gradually developed and innovated through interactions among technologies, institutions, and interpretations of landscape (external) pressures, with the industry’s ambitions of becoming more sustainable. The case history presents salmon farming as an example of an incremental transformation with gradual reorientations. Aquaculture developed from a niche innovation in the agricultural sector in the 1960s into a sociotechnical regime of its own. The shift from wet feed to dry, extruded feed was a crucial technological enabler. At the start of the 1990s, strong exogenous changes, including an economic crisis of overproduction and declines in salmon prices, led to extensive institutional changes. Shifts in ownership and the introduction of feed quotas brought a substitution pathway, whereby salmon farming became a national economic project. As production recovered, however, overfishing for feed became a concern. From the late 1990s on, the sociotechnical regime followed a reconfiguration pathway with the innovation of soy as a feed input. Over time, using vegetarian salmon feed has had unintended consequences, particularly environmental and social problems related to soy production. This case exhibits a shift in transition pathways and in interpretations of sustainability. Neither technologies nor transitions in themselves are sustainable; institutions and actors are unable to create sustainable alternatives. Together, however, they have managed to make the fish farming industry take heed to different sustainability concerns over time. Yet, the transition to soy-based salmon feed demonstrates only a weak sustainability and with a main focus on economic sustainability. This finding is line with the critique of the bioeconomy agenda for paying insufficient attention to environmental sustainability and for failing to challenge predominant structures in society.